Decreased osteoblasts and increased osteoclasts in rats after coal dust exposure (Universa Medicina, 2011)
Bone remodeling is a physiological process of cortical and trabecular bone reconstruction, with initial bone resorption, by osteoclasts and concurrent bone formation by osteoblasts. Oxidative stress due to coal dust exposure is not only found in the lungs, but also in the circulation or systemically. The aim of this study was to determine the effect of oxidative stress from coal dust exposure on the number of osteoblasts and osteoclasts in rats. In this experimental study, four groups were evaluated: control; coal dust exposure at 6.25 mg/m3 for 28 days; coal dust exposure at 12.5 mg/m3 for 28 days; coal dust exposure at 25 mg/m3 for 28 days (all exposures were given daily for one hour). Circulatory oxidative stress was measured by malondialdehyde level. Osteoblast and osteoclast numbers were counted by light microscopic examination of distal femoral cross-sections stained with hematoxylin eosin. This study showed that malondialdehyde levels were significantly increased in coal dust exposure groups, in comparison with the control group (p